Odpowiedzi

2009-10-26T14:46:56+01:00
(2x+3)² - (3x-4)² = 4x²+9+12x -(9x²+16-24x)= 4x²+9+12x -9x² -16+24x= -5x²+36x -7


(7a-1)² - (4+2a)² = 49a²+1-14a -(16+4a²+16a)= 49a²+1-14a -16-4a²-16a=
45a²-30a-15

(4y + 2z)² - (3z+5y)² = 16y²+4z²+16yz -(9z²+25y²+30yz)= 16y²+4z²+16yz -9z²-25y²-30yz= -9y²-5z²-14yz

-3(3c-2d)² = -9c²+6d²

2(5x+3)² - 3(4-7x)² = 50x²+18+60x- 48+147x²+84x= 197x²+144x -30
Najlepsza Odpowiedź!
2009-10-27T09:17:33+01:00
(2x+3)²-(3x-4)²=4x²+12x+9-(9x²-24x+16)=4x²+12x+9-9x²+24x-16=-5x²+36x-7

(7a-1)²-(4+2a)²=49a²-14a+1-(16+16a+4a²)=49a²-14a+1-16-16a-4a²=45a²-30a-15

(4y+2z)²-(3z+5y)²=16y²+16yz+4z²-(9z²+30zy+25y²)=16y²+16yz+4z²-
9z²-30zy-25y²=9y²+16yz+13z²-30zy

-3(3c-2d)²=-3(9c²-12cd+4d²)=-27c²+36cd-12d²

2(5x+3)²-3(4-7x)²=2(25x²+30x+9)-3(16-56x+49x²)=50x²+60x+18-48+168x-147x²=-97x²+228x-30